Strategy of the School Principle in Increasing Teacher Loyalty at Ash-Shofa SDIT Cikarang Barat, Bekasi District - Senaeni; Suharyat, Yayat; Apriliantoni (Proceeding International Conference on Education, 2023)
This research aims to learn how preacher coaching is handled in the community service program at STID Mohammad Natsir. A qualitative technique is used in this investigation. Using interviews, observations, and documentation to acquire data. Analysis of data with Miles and Huberman. Data and source triangulation are utilized to verify the accuracy of the data. The study found several problems. Some people thought the preachers were Wahhabis or Salafis because they didn't understand their da'wah's fiqh, and there was no guide to fiqh books of worship specifically for students. This program isn't working well because there isn't enough information about where preaching will take place. As a result, the incorrect people are sent to the wrong places, and there are budget issues. This study concludes that the da'i must be better managed, particularly when knowing fiqh, obtaining accurate location information, and creating a budget.